P055 Vedolizumab Treatment Persistence up to 5 Years: Post hoc Analysis in Vedolizumab-Naïve Patients From the GEMINI Long-Term Safety Study. (December 2019) - Loftus, Edward; Peyrin-Biroulet, Laurent; Vermeire, Séverine; Adsul, Sashi; Demuth, Dirk; Mokiou, Stella; Patel, Haridarshan; Lirio, Richard
Abstract : BACKGROUND: Vedolizumab (VDZ) is a gut-selective, humanized monoclonal antibody approved for moderately to severely active ulcerative colitis (UC) and Crohn's disease (CD). Although VDZ efficacy and safety are well established, there are limited publications on longer-term (>3 years) treatment persistence. This study evaluated VDZ treatment persistence for up to 5 years in a GEMINI long-term safety (LTS) VDZ de novo cohort. METHODS: All patients in GEMINI LTS (NCT00790933) were treated with VDZ every 4 weeks. A post hoc analysis of data from patients not previously treated with VDZ before Week 0 of GEMINI LTS (de novo cohort) was conducted, with VDZ treatment persistence assessed using Kaplan-Meier survival analysis. Treatment discontinuations due to adverse events (AEs) or lack of efficacy were considered for the analysis; discontinuations due to protocol deviation, patient withdrawal, or loss to follow-up were censored. Treatment persistence analyses were further stratified by Week 12 treatment response (primary response/nonresponder), prior anti-tumor necrosis factor (anti-TNF) failure (Yes/No), type of anti-TNF failure (primary/secondary nonresponse), and concomitant therapy (corticosteroids, 5-aminosalicylates, immunomodulators, or their combinations) at baseline (Yes/No); a log-rank test assessed statistical differences between subgroups. RESULTS: The GEMINI LTS de novo cohort included 421 patients (UC 190; CD 231) with a mean disease duration of 8.7 (UC) and 10.6 (CD) years, 6.0 mean partial Mayo score (UC) and 11.1 mean Harvey-Bradshaw Index; 61% of patients with UC and 74% with CD had prior anti-TNF failure. Up to 5 years follow-up, 276 patients (66%) total discontinued VDZ: 16% with UC and 17% with CD due to AEs, and 24% with UC and 33% with CD due to lack of efficacy. Survival probabilities for VDZ treatment persistence at 54 months were 53% for UC and 41% for CD. These VDZ 54-month survival probabilities were higher in patients with VDZ treatment response at Week 12 vs without (UC, 60% vs 26%, respectively, P < 0.0001; CD, 42% vs 35%, respectively, P = 0.001) and in patients without prior anti-TNF failure vs with (UC, 63% vs 47%, respectively, P = 0.046; CD, 47% vs 42%, respectively, P = 0.016). Among patients with baseline anti-TNF failure, survival probabilities for VDZ treatment persistence at 54 months were higher in UC patients who were secondary nonresponders vs those who were primary nonresponders (65% vs 15%, respectively, P < 0.0001); this difference was not observed in CD patients (44% vs 40%, respectively, P = 0.573). There were no differences in survival probabilities of continuing VDZ at 54 months among patients with UC or CD who initiated VDZ therapy with vs without any concomitant medications. CONCLUSION(S): More than half of patients with UC and 4 of every 10 patients with CD persisted on VDZ for 54 months. Treatment persistence rates in UC and CD cohorts were significantly higher in Week 12 responders and patients without prior anti-TNF failure, whereas there were no differences in persistence rates with baseline use of concomitant medications. Vedolizumab discontinuation rates due to AEs were low. These findings from GEMINI LTS support the longer-term effectiveness and safety of VDZ in patients with moderately to severely active UC and CD.